Oxford international secondary Science workbook grade 6 - Fullick, Ann (Karachi : Oxford university press, 2023)
The Oxford International Secondary Science Workbook 6 (Second Edition) complements the Student Book by providing additional practice and reinforcement of key scientific concepts. It includes a variety of exercises, such as review questions, investigations, and critical thinking tasks, covering topics in biology, chemistry, physics, and the environment. The workbook is designed to help students consolidate their understanding through hands-on activities, problem-solving tasks, and self-assessment opportunities. Aligned with international curricula, it supports inquiry-based learning and enhances students' scientific knowledge and skills.
Keywords: Science : Workbook; Oxford : Second edition